1998
DOI: 10.1021/np970124y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Elucidation of Two Plant Ecdysteroids, Gerardiasterone and 22-Epi-20-hydroxyecdysone

Abstract: Two minor plant ecdysteroids, 22-epi-20-hydroxyecdysone (1) and gerardiasterone (2), were isolated from Serratula tinctoria L. (Compositae). The first compound, a new natural product, was characterized by an unusual stereochemistry at C-22 (i.e., 22S). The second compound was identified as (20R,23S)-20,23-dihydroxyecdysone, a compound previously isolated from the Zooanthid Gerardia savaglia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…One of the most common and abundant ecdysteroids, 20-hydroxyecdysone (20-HE), is found in many plants including widely cultivated species like Spinacia oleracea (spinach) (Bathori, Mathe, Girault, Kalasz, & Lafont, 1998). Ecdysteroids have also been reported to have effects in mammals, including lowering cholesterol levels and blood glucose (Dinan, Harmatha, Volodin, & Lafront, 2009;Mironova, Kholodova, Skachkova, Bondar, & Datsenko, 1982;Yoshida, Otaka, Uchiyama, & Ogawa, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common and abundant ecdysteroids, 20-hydroxyecdysone (20-HE), is found in many plants including widely cultivated species like Spinacia oleracea (spinach) (Bathori, Mathe, Girault, Kalasz, & Lafont, 1998). Ecdysteroids have also been reported to have effects in mammals, including lowering cholesterol levels and blood glucose (Dinan, Harmatha, Volodin, & Lafront, 2009;Mironova, Kholodova, Skachkova, Bondar, & Datsenko, 1982;Yoshida, Otaka, Uchiyama, & Ogawa, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…20) On the basis of these results, it is feasible to conclude that the stereochemistry of the hydroxy group at C-22 is of pivotal importance for the molting hormonal activity. Even though 21) Hedtmann et al reported that their synthetic 22-epi-20E showed neither ES receptor binding nor molting hormonal activity.…”
Section: Cs/poa Hybrid Compoundsmentioning
confidence: 98%
“…Based on the spectral analysis ( [8,9]. However, this is the first time this structure or compound was established in Vitex doniana sweet.…”
Section: Test For Terpenoidsmentioning
confidence: 99%